Evaluation of the Effect of Polybutester and Polypropylene Sutures on Complications after Impacted Lower Third Molar Surgery - Zeynep Dilan Orhan; Levent Ciğerim (Applied Sciences, 2024)
Complications that can occur in the postoperative period of impacted lower third molar extraction are factors that have an impact on the daily routine of patients. This study aimed to evaluate the efficacy of polybutester and polypropylene sutures on postoperative complications after impacted lower third molar surgery. Two different suture materials were used in the 35 patients with bilateral impacted lower third molars included in the study: polybutester sutures in group 1 and polypropylene sutures in group 2. Measurements were taken to evaluate swelling and trismus before surgery and on the 2nd and 7th days after surgery, and pain was evaluated using a visual analogue scale (VAS), which patients were asked to complete after surgery. Wound healing, suture-related injury and suture-related discomfort in patients were also evaluated. The pain and suture-related discomfort felt on the side where the polybutester suture was used was less on the second postoperative day than on the side where the polypropylene suture was used. These results support the use of polybutester sutures in impacted third molar surgery.